Studi Kasus Faktor Penyebab Low-Self Confidence Pada Siswa Kelas 1/4 Mutawasit Arunsat Vitaya School Saiburi, Pattani, Thailand Selatan - Yulianti Yulianti; Bulkani Bulkani (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This study aims to determine the factors causing low self-confidence in 1/4 Mutwasit Arunsat Vittaya School class students, in Payo, Saiburi, Pattani, Southern Thailand. The approach used in the study of the causes of Low-Self Confidence in 1/4 Mutwasit Arunsat Vittaya School students, in Payo, Saiburi, Pattani, Southern Thailand is a qualitative approach to the type of case study. The results of this study indicate that the causes of Low-Self Confidence in 1/4 Mutwasit Arunsat Vittaya School, in Payo, Saiburi, Pattani, Southern Thailand consist of internal and external factors. The internal factors include self-concept, self-esteem, physical condition, and life experience. While external factors include education, work and the environment